PAK6-mediated phosphorylation of PPP2R2C regulates LRRK2-PP2A complex formation - Iannotta, Lucia; Emanuele, Marco; Favetta, Giulia; Tombesi, Giulia; Vandewynckel, Laurine; Lara Ordóñez, Antonio Jesús; Saliou, Jean-Michel; Drouyer, Matthieu; Sibran, William; Civiero, Laura; Nichols, R. Jeremy; Athanasopoulos, Panagiotis S.; et al. (Frontiers in Molecular Neuroscience, 2023)
Mutations in leucine rich repeat kinase 2 (LRRK2) are a common cause of inherited and sporadic Parkinson's disease (PD) and previous work suggests that dephosphorylation of LRRK2 at a cluster of heterologous phosphosites is associated to disease. We have previously reported subunits of the PP1 and PP2A classes of phosphatases as well as the PAK6 kinase as regulators of LRRK2 dephosphorylation. We therefore hypothesized that PAK6 may have a functional link with LRRK2's phosphatases. To investigate this, we used PhosTag gel electrophoresis with purified proteins and found that PAK6 phosphorylates the PP2A regulatory subunit PPP2R2C at position S381. While S381 phosphorylation did not affect PP2A holoenzyme formation, a S381A phosphodead PPP2R2C showed impaired binding to LRRK2. Also, PAK6 kinase activity changed PPP2R2C subcellular localiza tio n in a S381 phosphorylation-dependent manner. Finally, PAK6-mediated dephosphorylation of LRRK2 was unaffected by phosphorylation of PPP2R2C at S381, suggesting that the previously reported mechanism whereby PAK6-mediated phosphorylation of 14-3-3 proteins promotes 14-3-3-LRRK2 complex dissociation and consequent exposure of LRRK2 phosphosites for dephosphorylation is dominant. Taken together, we conclude that PAK6-mediated phosphorylation of PPP2R2C influe nces the recruitment of PPP2R2C to the LRRK2 complex and PPP2R2C subcellular localization, pointing to an additional mechanism in the fine-tuning of LRRK2 phosphoregulation.